Using balm-ii for Deriving Cascade Parallel Composition of Timed Finite State Machines - M. L. Gromov; N. V. Shabaldina (Моделирование и анализ информационных систем, 2016)
In this paper, we consider the problem of deriving a cascade parallel composition of timed ﬁnite state machines (TFSMs). In order to build such a composition we can derive the corresponding binary parallel compositions step-by-step. It is known that if each component of a binary parallel composition is TFSM with output delays that are natural numbers or zero, the result of the composition can be TFSM with output delays that are sets of linear functions. So, the problem of deriving a cascade composition of TFSMs with constant output delays is reduced to the problem of deriving several binary parallel compositions of TFSMs with output delays that are sets of constants or linear functions. In this work, we reﬁne the deﬁnition of TFSM and pay special attention to the description of an output delay function. As a tool for deriving the composition we consider balm-ii, and in consequence we study the ways of constructing the corresponding automaton for TFSM with output delays as a set of linear functions. We suggest a new procedure for constructing such an automaton, and unlike the known procedure our procedure does not require further determinization of the derived automaton. Moreover, we describe step by step how to build the composition of the derived automaton by using balm-ii, and discuss a procedure of reverse transformation from the global automaton to TFSM in case when the components are TFSMs with output delays that are sets of linear functions. We use an application example in order to illustrate derivation of the cascade parallel composition of TFSMs.